Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967